Cocoa Productivity as a Moderating Variable in the Relationship between Maintenance Costs and Farmer Welfare: JEL Classification: Q12, Q13, Q16, O13, D24 - Azis, Akbar; Karim, Ahmad; Hapri, Muhammad Alwi (Newinera Publisher, 2025)
This study aims to analyze the effect of maintenance costs on the welfare of cocoa farmers in Manyamba Village, Tammerodo Sendana District, and to examine the role of cocoa productivity as a moderating variable in this relationship. The research method used a quantitative approach with a population of 60 cocoa farmers who also served as the research sample. Data were collected through observation, interviews, documentation, and questionnaires, then analyzed using the Partial Least Squares (SmartPLS) technique. The results showed that maintenance costs had a positive and significant effect on farmer welfare. Cocoa productivity was also shown to have a significant positive effect on improving welfare. However, the results of the moderation effect test showed that productivity did not play a significant role in strengthening or weakening the relationship between maintenance costs and farmer welfare. These findings confirm that efforts to improve farmer welfare depend not only on managing maintenance costs and productivity, but also require support from other external factors such as access to financing, agricultural technology, and government policies.